Impact of the Low Temperature Gate Dielectrics on Device Performance and Bias-Stress Stabilities of a-IGZO Thin-Film Transistors. (1st January 2015) - Nag, Manoj; Bhoolokam, Ajay; Steudel, Soeren; Genoe, Jan; Groeseneken, Guido; Heremans, Paul
Abstract : In this work, amorphous indium-gallium-zinc-oxide (a-IGZO) thin-film transistor's (TFT) characteristics with five different gate dielectrics (PECVD SiO2, PECVD SiNx, ALD Al2 O3, PVD SiO2 and PVD Al2 O3 ) deposited at temperature lower than 250°C have been studied. Their characteristics are compared to the TFTs with thermally grown SiO2 as gate dielectric. Among them, ALD Al2 O3 gate dielectric based a-IGZO TFTs showed comparable characteristics to the thermally grown SiO2 dielectric based TFTs. PECVD SiO2, PECVD SiNx, PVD SiO2 and PVD Al2 O3 dielectric based TFTs showed inferior characteristics. We attributed this to good electrical, morphological and chemical properties of ALD Al2 O3 dielectric layer compare to PECVD SiO2, PECVD SiNx, PVD SiO2 and PVD Al2 O3 dielectric layers.